A novel ankle rehabilitation device based on a reconfigurable 3-RPS parallel manipulator. (April 2019) - Nurahmi, Latifah; Caro, Stéphane; Solichin, Mochamad
Highlights: Derivation of design conditions related to the base and moving-platform and 3-dof operation modes. Parametrization of orientation workspace and determination of actuation singularity loci in both Polar and Cartesian coordinates. Performance index named Maximum Inscribed Circle Diameter (MICD) and its distribution in the design parameter space. Dimension synthesis based on MICD for five distinct moving-platform heights. Reconfiguration strategy to ensure the moving-platform working above the minimum required orientation for any moving-platform height. Abstract: This paper deals with the constraint-based design, optimum design and reconfiguration strategy of a 3-RPS parallel manipulator. Some design conditions related to the base and moving-platform design parameters and the three degree-of-freedom operation modes are derived. A 3-RPS parallel manipulator with two types of operation modes is generated by following those conditions. Due to its potential advantages, this manipulator is used as an ankle rehabilitation device which can cover the ankle joint motion. To derive the optimum parameters, kinematic optimization is conducted by initially parametrizing the orientation workspace and it turns out that its orientation workspace is not symmetrical. The singularity loci are traced in its orientation workspace. A performance index, named Maximum Inscribed Circle Diameter (MICD) is presented to assess the maximum tilt of the moving-platform for any azimuth angle. The distributions of MICD are plotted in the design space for different moving-platform heights. The optimum region with regard to MICD is obtained. It is noteworthy that the evolution of MICD as a function of moving-platform height in both operation modes is the opposite. Therefore, a reconfiguration strategy is proposed to ensure the moving-platform working above the minimum required orientation for any moving-platform height.